Prevalence of Self-Reported Halitosis and Associated Factors: A Cross-Sectional Study among Dental Patients - Marina Alievi; Stêvan da Silva Freitas; Rafaela Cherobini Moresco; Lilian Rigo (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To determine the prevalence of self-reported halitosis among patients attending the dental clinic of a university in southern Brazil and identify associated factors. Material and Methods: The sample of this cross-sectional study included 269 individuals over 18 who attended the clinic for six months. A questionnaire was used to collect data on self-reported halitosis, sociodemographic characteristics, oral hygiene habits, medication use, systemic diseases, smoking and drinking habits, and self-perception of oral health. The relative and absolute frequencies of the variables were analyzed, and multivariate binary logistic regression analysis was performed to obtain odds ratios (OR) and respective 95% confidence intervals (95%CI) at p < 0.05. Results: The mean age of the sample was 44.86 (±16.55), and 65% were female. The study found a self-reported prevalence of halitosis of 27.9%. Individuals who reported xerostomia were more likely to have self-reported halitosis (OR=2.15; 95% CI: 1.22-3.78). Furthermore, those who visited the dentist more than a year ago were more likely to have self-reported halitosis compared to those who visited no more than six months ago (OR=1.93; 95% CI: 1.09-3.41). Conclusion: The study showed a high prevalence of self-reported halitosis among patients and revealed an association with individuals who reported having xerostomia and who have been attending dental appointments for a longer time.